Effects of Adolescent Crisis on Girls’ Secondary Schools’ Academic Performance in Vihiga County in Kenya and the Implication of Guidance and Counseling - Constance M. Amusala (Research Aspects in Arts and Social Studies Vol. 9, 2023)
Adolescence is a period of transition in which all of the human doubts, hesitations, and uncertainties manifest. Secondary school girls’ academic problems in Kenya have been linked to the adolescence crisis. The purpose of the study was to investigate the influence of adolescent crisis on two girls’ secondary schools’ academic performance in Vihiga County in Kenya and the implication of guidance and counseling. The quantitative data collected was analysed using the statistical package for social sciences (SPSS). The qualitative data gathered was organized, coded, and analyzed to supplement, explain, and interpret quantitative data gathered from the same environment. Findings of this study served as a contribution in the area of education as a whole, the Ministry of Education, school administration, parents and other stakeholders involved with adolescents especially with girls within the area of study.